Analisis Program Fakem Aktib Dalam Kegiatan Kemanusiaan Pada Masyarakat Lrg. Khotib Kel 7 Ulu Kota Palembang - Alawiyah, Tuti; Hasmawati, Fifi; Isnaini, Mohd. Aji (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Humans cannot live alone so humans need other people to grow and develop, especially in improving the quality of life. One way to improve the quality of life is by joining or participating in several associations or organizations such as the Aktib Humanitarian Charity Forum. The humanitarian charity forum is a forum for social activities owned by residents of the 7 ulu sub-district, to be precise, at lrg. Khotib Palembang city which is an informal organization that provides services to members of the community. The method used in this research is qualitative method. The type of data used is primary and secondary data. Data collection techniques in this study were carried out through observation, interviews, and documentation. The results obtained from this study, first regarding program activities carried out by the Fakem Aktib organization include, Providing compensation to disaster experts when Fakem Aktib members have a death accident, Providing services to disaster experts in the form of ambulances, Serving Fakem Aktib members in terms of good events in the form of Invertaris items to be loaned to Fakem Aktib members who have celebrations, during the holy month of Ramadan Fakem Aktib management works together with the management of the blessing mosque to hold iftar together, carry out tarawih, and dawn lectures, hold qurban gatherings with fellow members and the public when the Eid alFitr holiday approaches adha, Carrying out the August 17 competition activities, both in the form of events for children, adults, and mothers. Furthermore, regarding the Fakem program analysis of humanitarian activities in the lrg.khotib community, namely that it is going very well and is very helpful for disaster experts in need. Starting from how to overcome obstacles to active Fakem activities, namely by appealing to members to immediately pay off arrears and invite Fakem members to attend and stay in touch with disaster experts. The Fakem Aktib management structure is carried out on the basis of consensus agreement to form a Fakem Aktib management structure which is formed once a year and holds an annual meeting of Fakem Aktib members every December 25th and receives income from active Fakem members. The community's response to this Fakem Aktib activity was very good and community participation regarding this Fakem Aktib activity was also very enthusiastic. Borrowing invertaris items for wedding celebrations or thanksgiving events all have to pay cash, but if someone gets into a disaster or for a gift everything is free.